MANAGEMENT ALLOWABLE DEPLETION (MAD) LEVEL FOR WATER USE EFFICIENCY OF CHILI ON TYPIC KANHAPLUDULTS AT TAMANBOGO, LAMPUNG - HARYATI, UMI; SINUKABAN, N; MURTILAKSONO, K; ABDURACHMAN, ADI (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2010)
Water scarcity is the main factor causing crop production decrease and harvest failure in the upland areas. To improve water use efficiency by plants, Management Allowable Depletion (MAD) concept can be applied. MAD is the degree of soil dryness that still lead to optimum crop yied. This research was aimed to: 1) determine a correct MAD-level in order to achieve the optimum water use efficiency and 2) evaluate the effect of irrigation water sources on water use efficiency. The research was carried out on a Typic Kanhapludults at Tamanbogo Experimental station, East Lampung in dry season of 2005. Chili (Capsicum annum) was use as an indicator crop. The size of experimental plot was 5 x 10 m, that was arranged in split-plot design with 3 replications. The treatments were irrigation water sources designed as main plot which consisted of: A1 = ground water A2 = surface water, while MAD-level was designed as sub-plot, which consisted of : I1 = 20% of available water, I2 = 40% of available water, I3 = 60% of available water, I4 = 80% of available water, and I5 = 100% of available water. Irrigation was provided to reach 80, 60, 40, and 20% available water respectively. For the I5 treatment, irrigation was applied every day. The results showed that MAD-level of 60% of available water (I3) with the average of 9.6 mm of irrigation water, applied every three days, gave themost optimum crop yield and water use, thus achieving the highest water use efficiency. The surface irrigation water had a better quality than ground water,leading to a better plant growth, a higher crop yield and a higher water use efficiency than ground water